2021
DOI: 10.1038/s41537-021-00153-4
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal assessment of communicative-pragmatic features in schizophrenia: a machine learning approach

Abstract: An impairment in pragmatic communication is a core feature of schizophrenia, often associated with difficulties in social interactions. The pragmatic deficits regard various pragmatic phenomena, e.g., direct and indirect communicative acts, deceit, irony, and include not only the use of language but also other expressive means such as non-verbal/extralinguistic modalities, e.g., gestures and body movements, and paralinguistic cues, e.g., prosody and tone of voice. The present paper focuses on the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 102 publications
2
8
0
Order By: Relevance
“…At a behavioral level, patients showed more difficulty than HC under all three experimental conditions, especially in irony understanding. This result is in accordance with previous pragmatic studies carried out on subjects with SZ ( Brüne and Bodenstein, 2005 ; Mazza et al, 2008 ; Colle et al, 2013 ; Bambini et al, 2016 ; Bosco et al, 2019 ; Parola et al, 2021b ). Moreover, we found that both patients and HC demonstrated greater difficulties in the correct comprehension of deceptive and ironic experimental conditions compared to the sincere one.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At a behavioral level, patients showed more difficulty than HC under all three experimental conditions, especially in irony understanding. This result is in accordance with previous pragmatic studies carried out on subjects with SZ ( Brüne and Bodenstein, 2005 ; Mazza et al, 2008 ; Colle et al, 2013 ; Bambini et al, 2016 ; Bosco et al, 2019 ; Parola et al, 2021b ). Moreover, we found that both patients and HC demonstrated greater difficulties in the correct comprehension of deceptive and ironic experimental conditions compared to the sincere one.…”
Section: Discussionsupporting
confidence: 93%
“…Deficits in social cognition and more specifically in communication have an important impact on the real-life functioning of people with schizophrenia (SZ) ( Fett et al, 2011 ; Javed and Charles, 2018 ; Green et al, 2019 ). In particular, patients suffering from SZ have shown a wide range of deficits in the communicative-pragmatic domain, characterized by a severe impairment of the comprehension of the speaker’s communicative intention in everyday conversational interactions ( Brüne and Bodenstein, 2005 ; Mazza et al, 2008 ; Colle et al, 2013 ; Bambini et al, 2016 ; Bosco and Parola, 2017 ; Bosco et al, 2019 ; Parola et al, 2018 , 2021a , 2021b ; Pawełczyk et al, 2018 ). Communicative-pragmatics, i.e., the ability to use language to convey meaning in a specific context ( Levinson, 1983 ), is linked to the Theory of Mind (ToM), i.e., the ability to attribute mental states to oneself and others, however, these two abilities do not completely overlap ( Bambini et al, 2016 ; Bosco et al, 2018 , 2019 ; Parola et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ABaCo is made up of five different evaluation scales-linguistic, extralinguistic, paralinguistic, context, and conversationalinvestigating participants' communicative-pragmatic ability. The ABaCo has shown in previous research to be a valid tool for investigating communicative-pragmatic ability in patients with traumatic brain injury [54][55][56][57][58][59], schizophrenia [60][61][62][63][64][65], left and right acquired brain lesions [66,67]. We expected to observe age-related differences on the pragmatic performance on the ABaCo in the three groups of participants, from the oldest (poorest performance) to the youngest group (best performance).…”
Section: Introductionmentioning
confidence: 94%
“…This definition is more encompassing than the previous distinction between direct and indirect speech acts proposed by the SPM (Searle, 1975). This distinction has proven particularly useful for studying how pragmatic performance can vary as a function of increasing inferential complexity in clinical populations, such as those with traumatic brain injury (Bosco, Parola & Sacco et al, 2017), schizophrenia (Bosco et al, 2019; Parola et al, 2018), right (Parola et al, 2016) and left (Gabbatore et al, 2014) hemisphere damage, and also for assessing the comprehension of different communicative phenomena and expressive modalities in these populations (Bosco, Gabbatore, et al, 2018; Bosco, Parola, et al, 2018; Parola, Brasso, et al, 2021; Parola et al, 2020; Parola, Gabbatore, et al, 2021). This study provides additional support for this distinction and its utility, for example, in the clinical assessment of communicative-pragmatic deficits (see Angeleri et al, 2008; Bosco, Parola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%